Re-Locating the Spaces of Television Studies - Pertierra, Anna Cristina (2016)
This paper will extend work originally presented in Pertierra and Turner’s Locating Television (2013) to argue that the reasons for which the demise of television was prematurely assumed can be understood and corrected by critically examining the geopolitics of television scholarship. The spaces from which television has been taken seriously as a topic of investigation have enabled a neglect of empirical and theoretical research that genuinely engages with the ways in which television might be understood as variously surviving, growing, innovating and even leading the current and future global media landscapes. The paper offers two ways in which television scholars might productively re-locate their spheres of concentration to understand the diversity of television worlds today: 1) empirically, it considers the case of the Philippines where broadcast television is successful in ways that could only be dreamed of by television executives in the so-called ‘world centres’ of the global entertainment industry. 2) theoretically, the paper refers to complementary attempts in sociology, literary and cultural studies to offer alternatives to Europe and North America from which scholars might locate the vanguard for modernity, globalization and innovation. It is by engaging with both of these strands in concert—empirically investigating television beyond the ‘usual places’ in such a way that responds to the call of cultural theorists to question our very assumptions about where television studies’ ‘usual places’ should be, that more nuanced understandings, and fewer premature declarations, might be made about what television is, and where it is going.